Forensic metrology scientific measurement and inference for lawyers, judges and criminalists - Vosk, Ted; Emery, A. F. (International forensic science and investigation series, 2015)
Forensic metrology is the application of scientific measurement to the investigation and prosecution of crime. Forensic measurements are relied upon to determine breath and blood alcohol and drug concentrations, weigh seized drugs, perform accident reconstruction, and for many other applications. Forensic metrology provides a basic framework for the performance and critical evaluation of all forensic measurements.